The Environmental Compensation Fund: Bridging Liability Gaps in the Deep Seabed Mining Regime. Issue 6 (2nd November 2021) - Xu, Xiangxin; Xue, Guifang (Julia)
Abstract: The current transition period from exploration to exploitation in deep seabed mining (DSM) has witnessed efforts on the part of the international community to draft regulations for the exploitation of mineral resources in the Area. The production of the "Draft Exploitation Regulations" has been a priority theme in recent International Seabed Authority (ISA) sessions. Although discussion in reducing environmental impacts has been central to the progressive instrument, some liability gaps and approaches to close such gaps have not come up with desirable solutions. Against this background, the paper underscores the need for an Environmental Compensation Fund (the Fund) to bridge these gaps under the DSM regime. The paper argues that the three provisions about the Fund envisaged in the Draft Exploitation Regulations fall short of adequate deliberation and operational details. To bridge up the liability gaps, some critical issues in operating the Fund need to be carefully considered regarding the establishment, purpose, contributions, and claims for compensation. The paper suggests that the ISA may take the key elements of existing compensation funds, inter alia, the IOPC Funds to improve the operation and function of this Fund.